2021
DOI: 10.1371/journal.pone.0246023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of meteorological factors on the activity of influenza in Chongqing, China, 2012–2019

Abstract: Background The effects of multiple meteorological factors on influenza activity remain unclear in Chongqing, the largest municipality in China. We aimed to fix this gap in this study. Methods Weekly meteorological data and influenza surveillance data in Chongqing were collected from 2012 to 2019. Distributed lag nonlinear models (DLNMs) were conducted to estimate the effects of multiple meteorological factors on influenza activity. Results Inverted J-shaped nonlinear associations between mean temperature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
(40 reference statements)
4
13
1
Order By: Relevance
“…However, conflicting views have been reported regarding the impact of RH on influenza. The findings of the current study on RH were not in line with those reported by studies in Poland, Zhejiang, and Chongqing, in which the influenza incidence was moderately positively correlated with RH, and higher RH could increase the risk of influenza incidence (42)(43)(44). The difference in the results may be because of the difference in the latitude, climate type, demographic characteristics of the study area, and the statistical methods and models used.…”
Section: Discussioncontrasting
confidence: 99%
“…However, conflicting views have been reported regarding the impact of RH on influenza. The findings of the current study on RH were not in line with those reported by studies in Poland, Zhejiang, and Chongqing, in which the influenza incidence was moderately positively correlated with RH, and higher RH could increase the risk of influenza incidence (42)(43)(44). The difference in the results may be because of the difference in the latitude, climate type, demographic characteristics of the study area, and the statistical methods and models used.…”
Section: Discussioncontrasting
confidence: 99%
“…The seemingly contradictory results further emphasize the complexity of the influence of climate factors and geographical environment on influenza activity. Air pressure was positively correlated with influenza activity, while influenza was negatively correlated with sunshine hours and daily mean wind speed, which was consistent with the results of Qi et al [ 65 ] and previous research in Lanzhou from 2005 to 2010 [ 66 ]. When the air pressure is higher, the diffused virus in the air and is not easy to dissipate, resulting in an increase in influenza patients.…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed higher test‐positive rates for RSV‐A, RSV‐B, and HRV among children in Chongqing compared with the other three cities, consistent with results from a study at a children's hospital in Chongqing during 2013–2018 31 . Meteorological factors in Chongqing have been shown to be associated with influenza and pertussis 32,33 …”
Section: Discussionmentioning
confidence: 99%